Murine Leukemia Virus Proteins Expressed on the Surface of Infected Cells in Culture - Buetti, Elena (1980)
Infection of JLS-V9 cells in culture with Rauscher murine leukemia virus induced the appearance on the cell surface of two classes of viral proteins: Rauscher murine leukemia virus gp70, and glycoproteins related to the viral core (gag) proteins with apparent molecular weights in sodium dodecyl sulfate polyacrylamide gels of 80 × 10(3) and 95 × 10(3). The latter proteins were identified by lactoperoxidase-catalyzed iodination of the cell surface and by metabolic labeling with [(3)H]mannose followed by immunoprecipitation with an antiserum directed against the major viral core protein, p30. Tryptic peptide maps of chloramine T-iodinated proteins indicated that 80 × 10(3) - and 95 × 10(3)-molecular-weight proteins were closely related. The 95 × 10(3)-molecular-weight protein from Rauscher murine leukemia virus-infected cells had a tyrosine fingerprint which was identical to that of the 95 × 10(3)-molecular-weight gag surface polyprotein of endogenous virus-producing AKR-A cells, suggesting that expression on the cell surface of glycosylated forms of gag precursor polyproteins may not be an exclusive property of leukemic thymocytes, but a more general phenomenon in murine leukemia virus infection. Tryptic fingerprint analysis of iodinated viral and cell-bound gp70's before and after desialylation indicated a lower level of glycosylation in the cell-bound gp70 population than in virions. Analysis of only surface-iodinated gp70 showed a simple pattern of exposed tryptic peptides which was very similar in Rauscher murine leukemia virus-infected cells and in AKR-A cells.